1988
DOI: 10.1161/01.cir.78.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Cine magnetic resonance imaging for evaluation of anatomy and flow relations in infants and children with coarctation of the aorta.

Abstract: Sixteen cine magnetic resonance imaging (MRI) studies were performed in 14 patients aged 1 week to 17 years (mean age, 46 months), who had coarctation of the aorta confirmed at angiography or surgery. Conventional echocardiographic-gated MRI was first performed in axial and rotated sagittal views and was used to identify the slice locations for cine MRI. Cine MRI was performed by gradient-recalled acquisition in steady state with a 300 flip angle, 12-msec echo time, 22-msec pulse repetition time, and a 128 x 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…A practical advantage of these findings is that both 3D MRA of the thoracic aorta and PVC-MRI flow analysis are established MRI techniques, are commonly used in clinical practice, and require relatively short acquisition and imageprocessing times. 9,[13][14][15][16][23][24][25][26] Moreover, both techniques have been evaluated in patients with CoA and were found to reliably assess aortic morphology and collateral vessels and to accurately quantify flow in the descending aorta. 9,13 Assessment of coarctation severity presents a clinical challenge.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A practical advantage of these findings is that both 3D MRA of the thoracic aorta and PVC-MRI flow analysis are established MRI techniques, are commonly used in clinical practice, and require relatively short acquisition and imageprocessing times. 9,[13][14][15][16][23][24][25][26] Moreover, both techniques have been evaluated in patients with CoA and were found to reliably assess aortic morphology and collateral vessels and to accurately quantify flow in the descending aorta. 9,13 Assessment of coarctation severity presents a clinical challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found good correlations between coarctation diameter by MRI and x-ray angiography. 10,14,15 For example, Riquelme and colleagues 14 showed a correlation coefficient of 0.99 between gradient echo cine MRI and angiography, whereas Simpson et al 15 and Mendelsohn et al 10 reported correlation coefficients of 0.9 and 0.91, respectively. Other groups have focused on the percent increase in descending aorta flow from collateral vessels to assess coarctation severity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This diagnosis can be made in infants using routine TTE, but in older or postoperative patients the area of interest is not easily accessible with TTE. Conventional MRI often already provides essential information [2,6,7,15,33,83,91,101,110,119]. Useful diagnosis and followup of coarctation with MRI does not necessarily require the combination of a high-field machine and the latest pulse sequences, but the estimation of the severity of the stenosis from the size of the signal void on GRE images appears hazardous [103].…”
Section: Coarctation Of the Aortic Arch And Brachiocephalic Anomaliesmentioning
confidence: 99%